FACTORS AFFECTING STOCK BETA IN LQ-45 COMPANIES FOR THE 2020-2021 PERIOD - Enny Istanti; Bramastyo Kusumo Negoro; Achmad Daengs GS (International Journal of Economics and Management Research, 2023)
The purpose of this study is to provide empirical evidence of the effect of financial leverage, earnings per share (EPS) and asset growth on beta stocks. Samples of this study are seven companies LQ45 index listed in Indonesian stock Exchange period 20 20 -20 2 1. The model used is multiple linear regression. The results show that asset growth has a significant effect on beta stocks, but financial leverage and earnings per share have no positive effect on beta stocks. While earnings per share have no significant effect on beta stocks and have a negative effect on beta stocks. The results in the study also show that financial leverage, earnings per share and asset growth have a significant effect on beta stocks simultaneously. The results have implications for prospective investors who want to invest in the stock market, especially in buying shares, should first consider asset growth factors because these factors prove to have a significant impact on stock beta.